Transgenerational Effects of pCO2-Driven Ocean Acidification on Adult Mussels Mytilus chilensis Modulate Physiological Response to Multiple Stressors in Larvae - Diaz, Rosario; Lardies, Marco A.; Tapia, Fabián J.; Tarifeño, Eduardo; Vargas, Cristian A. (Frontiers in Physiology, 2018)
The effect of CO2-driven ocean acidification (OA) on marine biota has been extensively studied mostly on a single stage of the life cycle. However, the cumulative and population-level response to this global stressor may be biased due to transgenerational effects and their impacts on physiological plasticity. In this study, we exposed adult mussels Mytilus chilensis undergoing gametogenesis to two pCO2 levels (550 and 1200 µatm) for 16 weeks, aiming to understand if prolonged exposure of reproductive individuals to OA can affect the performance of their offspring, which, in turn, were reared under multiple stressors (pCO2, temperature, and dissolved cadmium). Our results indicate dependence between the level of pCO2 of the broodstock (i.e. maternal effect) and the performance of larval stages in terms of growth and physiological rates, as a single effect of temperature. While main effects of pCO2 and cadmium were observed for larval growth and ingestion rates, respectively, the combined exposure to stressors had antagonistic effects. Moreover, we found a suppression of feeding activity in post-spawning broodstock upon high pCO2 conditions. Nevertheless, this observation was not reflected in the final weight of the broodstock and oocyte diameter. Due to the ecological and socioeconomic importance of mussels’ species around the globe, the potential implications of maternal effects for the physiology, survival, and recruitment of larvae under combined global-change stressors warrant further investigation.